Knowledge, attitudes and practices on oral health care of obstetricians and pregnant women in a tertiary hospital - Dagang, Norman Onyx T.; Kakumoto, Hiroshi B.; Yumul, Giselle S. (Adviser).
Recent studies show that poor oral health is associated with adverse pregnancy outcomes. Obstetricians are usually the first to come in contact with pregnant patients. Objectives: This study aimed to determine the knowledge, attitudes and practices on oral health care of obstetricians and pregnant women in a tertiary hospital. Methods: A self-administered questionnaire was handed out to obstetricians and pregnant women through convenience sampling. Results: Results show that majority of the obstetricians were knowledgeable on the implications of poor oral health on the pregnant women and had positive attitude to matters that benefit their patients. However, they were not able to apply it to their practice as part of prenatal care. The majority of the pregnant respondents were also aware that dental treatments while pregnant are safe and have positive attitude towards it but lacks in prioritizing oral health care. Conclusion: Both obstetricians and pregnant women appear to have the right awareness and enthusiasm about oral health care during pregnancy but both need a thrust to put it into action.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.